Analysis of The Knowledge Level of Sei Tuan Village Community Regarding Respiratory Tract Infections Before and After Health Education - Sabrina Edriati Tarigan; Raisah Adilah; Maziaturrahmah Maziaturrahmah; Nabila Hana; Ridmahsyah Widiya Sari; Mutia Azhari; Rehana Qari Hafizah; Maysara Edriani; Muhammad Iqbal Dalimunthe; Putra Apriadi Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Acute respiratory infections are contagious diseases that make people sick and kill them in developing countries. This study aims to determine how much the community knows about acute respiratory infections before and after getting some education about them. This research is quantitative descriptive research with a quasi-experiment design. The population in this study were all participants in counseling acute respiratory infections. The sample used in this study consisted of 30 respondents, selected using total sampling and primary data with pretest and posttest data collection tools. The results showed that age and education affect the level of knowledge. The level of good knowledge before and after the intervention was 53.4%, and it was 83.4% after the intervention. There was a 30% increase in knowledge before and after the intervention. Increasing public knowledge about health is a way to improve the degree of public health. It is strongly suggested that the North Sumatra Health Office keep helping people, especially those near the coast, with health counseling..